Respuesta :
A circle centered at [tex]O(a,b)[/tex] with radius [tex]R[/tex] (the length of [tex]OP[/tex]) has equation
[tex](x-a)^2+(y-b)^2=R^2[/tex]
which can be parameterized by
[tex]\vec c(t)=\langle x(t),y(t)\rangle=\langle a+R\cos t,b+R\sin t\rangle[/tex]
with [tex]0\le t\le2\pi[/tex].
The tangent line to [tex]\vec c(t)[/tex] at a point [tex]P(x_0,y_0)[/tex] is [tex]\frac{\mathrm dy}{\mathrm dx}[/tex] with [tex]x=x_0[/tex] and [tex]y=y_0[/tex]. By the chain rule (and this is where we use implicit differentiation),
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\frac{\mathrm dy}{\mathrm dt}}{\frac{\mathrm dx}{\mathrm dt}}=\dfrac{R\cos t}{-R\sin t}=-\dfrac{\cos t}{\sin t}[/tex]
At the point [tex]P[/tex], we have
[tex]x_0=a+R\cos t\implies\cos t=\dfrac{x_0-a}R[/tex]
[tex]y_0=b+R\sin t\implies\sin t=\dfrac{y_0-b}R[/tex]
so that the slope of the line tangent to the circle at [tex]P[/tex] is
[tex]\dfrac{\mathrm dy}{\mathrm dx}=-\dfrac{\frac{x_0-a}R}{\frac{y_0-b}R}=-\dfrac{x_0-a}{y_0-b}[/tex]
Meanwhile, the slope of the line through the center [tex]O(a,b)[/tex] and the point [tex]P(x_0,y_0)[/tex] is
[tex]\dfrac{b-y_0}{a-x_0}[/tex]
Recall that perpendicular lines have slopes that are negative reciprocals of one another; taking the negative reciprocal of this slope gives
[tex]-\dfrac1{\frac{b-y_0}{a-x_0}}=-\dfrac{a-x_0}{b-y_0}=-\dfrac{x_0-a}{y_0-b}[/tex]
which is exactly the slope of the tangent line.